1999
DOI: 10.1038/sj.ejcn.1600817
|View full text |Cite
|
Sign up to set email alerts
|

The association of diet and thrombotic risk factors in healthy male vegetarians and meat-eaters

Abstract: Objective: The aim of this study was to assess thrombosis tendency in subjects who were habitual meat-eaters compared with those who were habitual vegetarians. Design: Cross-sectional comparision of habitual meat-eaters and habitual vegetarians. Setting: Free living subjects. Subjects: One hundred and thirty-nine healthy male subjects (vegans n 18, ovolacto vegetarians n 43, moderate-meat-eaters n 60 and high-meat-eaters n 18) aged 20 ± 55 y who were recruited in Melbourne. Outcome measures: Dietary intake was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 35 publications
3
77
0
1
Order By: Relevance
“…Although a large number of cross‐sectional studies14, 15 have shown that concentrations of TC, LDL‐C, and TG were much lower in vegetarians than in omnivores, a few studies32, 33 have found no such relationships with HDL‐C and TG concentrations. A meta‐analysis of 12 observational studies with a total of 4177 participants revealed no evidence showing that HDL‐C concentrations differed in vegetarians and omnivores 34.…”
Section: Discussionmentioning
confidence: 99%
“…Although a large number of cross‐sectional studies14, 15 have shown that concentrations of TC, LDL‐C, and TG were much lower in vegetarians than in omnivores, a few studies32, 33 have found no such relationships with HDL‐C and TG concentrations. A meta‐analysis of 12 observational studies with a total of 4177 participants revealed no evidence showing that HDL‐C concentrations differed in vegetarians and omnivores 34.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 31 vegetarians and 58 omnivores, who satisfied inclusion/exclusion criteria and were willing to volunteer participated in the study. Vegetarians were defined as those who did not consume meat, chicken, fish or other flesh foods, any more than six times per year (Li et al, 1999). Among the vegetarian group, there were six vegans who also refrained from eating eggs and dairy products.…”
Section: Subjectsmentioning
confidence: 99%
“…Long-chain n-3 fatty acids have been found to have beneficial effects on the regulation of plasma lipid levels and cardiovascular function (Mori and Beilin, 2001). Higher levels of platelet aggregation were found in vegetarians when compared to their omnivorous counterparts (Li et al, 1999), and long-chain n-3 fatty acid supplementation has been shown to reduce platelet aggregation (Mezzano et al, 2000). DHA supplementation also induced a moderate reduction in the total or LDL-cholesterol:HDL-cholesterol ratio and a slight reduction in triglyceride concentration in vegetarians (Conquer and Holub, 1996).…”
Section: Introductionmentioning
confidence: 99%